Detection of Blood Transglutaminase Enzyme in Fish Surimi Based Product by Using Polymerase Chain Reaction (PCR) Method - A.R. Alina; Nurul A.S. Aqilah; M.H.M. Yusop; K.M.W. Syamsul; N.R.S.A. Syarifah; A.Siti Mashitoh; A.S. Nadia Syuhada; H.S. Ummi Syuhada; A.Nurul Farah Sakinah; A.H. Nurul Mawaddah; S.Nurulhuda; M.A. Kal-Kausar (IDOSI Publications, 2024)
Middle-East Journal of Scientific Research 13 (Approaches of Halal and Thoyyib for Society, Wellness and Health): 29-35, 2013